The Basic Training Needs Of Health Providers Toward Pandemic Preparedness and Response: Indonesian Case in Pandemic Covid 19 - Sugeng Eko Irianto; Atikah Adyas (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Health providers have the most important role on Pandemic Covid 19 case management and prevention at the health centre, hospital and communities, even though they are one of the vulnerable groups for contracting Coronavirus Disease 2019 due to close contact when providing direct health services to patients with Coronavirus Disease 2019. Basic training is one the efforts that are expected to increase the knowledge and skill of the health workers about pandemic covid 19 preparedness and response on prevention and infection control and personal protective equipment against pandemic covid 19 so that transmission to health workers at the health facilities can be prevent. The purpose of this study is to identify and analyse the government policy about the need of standardized and basic training of health providers. The methodology used is a literature reviewed of government policies and report on Pandemic Covid 19 preparedness and response in Indonesia, and related scientific journal. The result of reviewed found that the needs of basic training of health providers towards pandemic preparedness and response consist of case management, stress management, psychological self-care, intensive care, personal protective equipment, communication strategy, epidemiological surveillance, contact tracing, collection of specimens, laboratory examination, hygiene and sanitation protocol and isolation strategy.